Optical Oscillator Evaluation in Radio Test Bed - Integration and Phase Noise Characterization of a Microresonator-Based Optical Oscillator - Hiselius, David (My University, 2026)
Local oscillator (LO) phase noise presents significant challenges in achieving high capacity wireless communication at millimeter-Wave frequencies. Through optical frequency division (OFD), high-Q resonators may be leveraged to generate low phase noise microwave frequency signals. In this work, Kerr microresonator-based OFD was integrated as an LO source in a point-to-point link radio test bed. The frequency divider and amplifier used to facilitate integration of the optical oscillator into the radio test bed were characterized from a phase noise perspective. The optical os cillator was subsequently analyzed by correlating observations in the phase noise spectrum to known noise mechanisms. Finally, radio link performance for external local oscillator sources, including the optical oscillator under study, was compared to an unmodified channel. Results indicate that photodetection noise constituted the primary performance limitation of the optical oscillator implementation, resulting in a comparatively high phase noise floor (-145 dBc/Hz). The impact of noise intro duced by the frequency divider and amplifier on radio link performance is estimated to be minor; however, residual phase noise measurements are required to verify this assumption. In radio link measurements, the optical oscillator achieved signal-to noise ratios approximately 6 dB lower than those of the unmodified channel. The observed degradation in radio link performance is consistent with previous studies identifying the LO noise floor as a dominant limitation in wideband communication systems. As the oscillator demonstrated excellent near-carrier phase noise (-130 dBc/Hz @ 100 kHz) and established methods of photodetection noise mitigation exist, further investigation is warranted.
Keywords: optical frequency division, microwave photonics, phase noise, local oscillator